QadirVax-19: A multi epitope-based vaccine against COVID-19 - Misha Mukhtar; Professor (Associate) Muhammad Imran Qadir (Kuwait Journal of Science)
An outbreak of COVID-19, caused by a novel virus named SARS-CoV-2, has become a global challenge which needs to be addressed immediately. It has high rate of transmission and severity of the disease varying from person to person. Researchers are trying to find effective vaccines and therapeutic targets to control this novel type of coronavirus. In the present study, surface glycoprotein was used to identify B cell and T cell epitopes that have strong immunogenic potential. Highly conserved region of the surface glycoprotein was identified from seven related human coronaviruses. Epitopes and their prominent features were predicted by using immunoinformatics tools. Epitopes which have high binding energy were joined together through linker to form an epitope-based subunit vaccine construct. Molecular docking was performed by MOE to predict the binding energies of construct with B cell receptor, MHC Class I and MHC Class II receptors. The sequence of the multi-epitope construct finally came out as LQYGSFCTQLNRGPGPGTFGAGAALQGPGPGNFTTAPAICGPGPGHWFVTQRNFAAYQYIKWPWYI. It was named as QadirVax-19. Multi-epitope construct was highly antigenic along with proteasomal cleavage sites and full population coverage. The highest binding energies were obtained which shows that the construct has the ability to produce stronger humoral and immune response against structural glycoproteins of SARS-CoV-2. In-silico cloning of the construct revealed its stable expression in E. coli. The present study was concluded in designing of Multi Epitope-Based Vaccine against COVID-19.